Psicomotricidad fina como estrategia de aprendizaje de la preescritura en los niños de cuatro años de la I.E.I. N° 591 Modelo San Juan Bautista, Iquitos 2023 - Boullosa Melendez, Gregoria del Carmen (2024)
This document is titled “Fine psychomotor skills as a prewriting learning strategy in four year-old children of the Initial Educational Institution No. 591 Model – San Juan Bautista, which presents as a general objective to determine how the level of psychomotor skills is associated with fine with the level of learning application of prewriting in four-year-old boys and girls of the I.E.I. N° 591 Model – San Juan Bautista – Iquitos, 2023, determining that to achieve the results a quantitative research approach would be developed, oriented towards descriptive, correlation, as well as a non-experimental design, in a population of 99 boys and girls that are four years old, a probabilistic sampling was also applied, finding as a result that fine psychomotor skills are significantly related to the prewriting learning strategy. Likewise, that fine psychomotor skills are as good as the prewriting learning strategy, generating a significantly positive relationship when relating the study variables. Likewise, the test of goodness of fit to normality according to Kolmogorov-Smirnov, in which the p_value of the fine psychomotor variable and prewriting learning strategies are less than 0.05, so they have free distribution (p < 0 .05), then for the inferential analysis, the non parametric statistical test Spearman's rho (rs) was used to demonstrate the hypothesis, which has as a test statistic, Student's t with n-2 degrees of freedom. The result was that 53.5% (53) boys and girls obtained a good level of application of prewriting learning strategies, concluding the research stating that there is a significant relationship between the study variables, and that it is important to develop it efficiently. To obtain good results, recommending applying fine psychomotor skills in the development of learning strategies for prewriting texts in four-year-old children.